Persuasive speech acts in the Namibian National Assembly - Amakali, Justina Meluwa Latenda (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This paper examined the speech acts used by Namibian Members of Parliament (MPs) during parliamentary proceedings. The main aim of this paper was to explain speech acts and show their intended persuasive effects in parliamentary discourse. Austin (1962) introduced three types of speech acts, locutionary, illocutionary and perlocutionary. The paper attempted to critically demonstrate how MPs use persuasion strategies in their debates. These speech acts were uttered through assertives, directives, commissives, expressives, and declaratives, as classified by Searle (1969). A qualitative approach was used in this paper whereby the Hansard were used to collect data. A purposeful sampling focusing on some MPs was used. This paper was guided by two theories, Austins Speech Act Theory and Aristotles Theory of Rhetoric. The need to apply rhetorical skills in debates is widely advocated for. Although not all members of parliament have a wide knowledge of rhetoric, acquiring and employing skills on rhetoric are prominent aspects of parliamentary debates. The findings of the paper revealed that members of parliament have the potential to use a variety of persuasive strategies in their speech acts by means of some rhetorical devices. It was concluded that most MPs deliberately make use of these speech acts as a persuasive mechanism in their discourse. Being the first study in parliamentary discourse in Namibia with regards to rhetoric, it is considered to be unique and adds value in the field of linguistics. It also serves as a pioneering research to researchers in political rhetoric.